Childhood after COVID: Children’s Interests in a Flourishing Childhood and a More Communal Childrearing - Gheaus, Anca (Philosophical Inquiry in Education, 2022)
This article brings into relief two desiderata in childrearing, the importance of which the pandemic has made clearer than ever. The first is to ensure that, in schools as well as outside them, children have ample opportunities to enjoy goods that are particular to childhood: unstructured time, to be spent playing with other children, discovering the world in company or alone, or indeed pursuing any of the creative activities that make children happy and help them learn. I refer to these as “special goods of childhood.” The second desiderata is to turn childrearing into a more communal practice, with lesser parental monopoly of care. For this, we need to give children access to multiple caring adults, and thus more opportunities to form secure and protected relationships.